The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.31372/20190401.1035
|View full text |Cite
|
Sign up to set email alerts
|

Association between alcohol consumption and body mass index in university students

Abstract: Objective : The aim of this study was to determine the correlation between alcohol consumption and body mass index in university students in Eastern Thailand. Methods : Undergraduate students (19–23 years, n = 396) were randomly surveyed via questionnaires, which included general information, alcohol consumption, and unhealthy food consumption. Average daily alcohol consumption was then calculated from grams of ethanol consumed per day. A subject, who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
12
2
1
Order By: Relevance
“…Finally, it is well known that stressful events, including home confinement, may also induce people to greater consumption of alcoholic beverages [ 12 ], which promotes a positive energy balance and contributes to weight gain [ 13 ]. In a survey conducted in Poland during lockdown, alcohol consumption was increased in 14.6% of the sample, with higher rates of alcohol abuse in adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is well known that stressful events, including home confinement, may also induce people to greater consumption of alcoholic beverages [ 12 ], which promotes a positive energy balance and contributes to weight gain [ 13 ]. In a survey conducted in Poland during lockdown, alcohol consumption was increased in 14.6% of the sample, with higher rates of alcohol abuse in adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that smoking can also decrease BMI, while smoking cessation stimulates weight gain [21]. On the other hand, alcohol has been found to promote a positive energy balance and contribute to weight gain, increasing BMI [22]. BMI can also be influenced by refugees' cultural beliefs [23], sociodemographic [24], and socioeconomic status [20].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do those with higher Body Mass Index (BMI) have a higher chance of consuming tobacco and smoking [13,14], but also, non-smokers have healthier eating behaviors than smokers. Furthermore, relationships were established between an increase in the amount of alcohol consumed and an increase in BMI [15]. However, those who drank frequently but in smaller amounts had a lower BMI [16].…”
Section: Introductionmentioning
confidence: 99%